Use of information and communication technology in production and marketing among vegetable farmers in Peninsular Malaysia - Nor Rizan, Nor Haslina (2017)
The development and widespread usage of information and communication technologies (ICT) become more important especially in the knowledge economy to ensure the realisation of Vision 2020. The diffusion of ICT services serves the social and economic development of the country. The state of this industry spells out the viability for investors to invest in Malaysia. ICT usage has improved efficiencies among Malaysia enterprises and directly increased Malaysia’s competitiveness in the global economy. Majorityof economists agree that information and communication technologies explain a significant share of productivity gains in modern economic. The development of ICT, especially in gadgets and mobile applications has expanded exponentially.Hence, we can see nobody in the country from children to edults leave home without a gadget. This development is being observed among farm producers either for personal uses as well as in their production. This research attempts to identify the current levels of ICT that farmers use in production and marketing of vegetables, to determine a factor influencing the use of ICT among vegetable farmers, to evaluate the ICT contributions toward production and marketing of vegetables and to determine the socio economic variable influencing ICT use among vegetables farmers. This research employed modified Technology Acceptance Model (TAM) in an attempt to assess Malaysian vegetable farmers’ attitudes toward ICT usage. Face to face interviews was conducted with 300 farmers using a standard structured questionnaire. Descriptive, factor analysis and regression analyses were employed to obtain the required results and objectives.The average farmers’ age is 41 years old while average of farm size is 2.0 hectares. The mean farming experience is 12.67 and the ICT use per day is 96 minutes. The majority of farmers have education up to secondary school. Most used ICT tools by vegetable farmers are hand phones, smartphones, fixed line, tablet, computer, and fax machine. They are used to get agriculture information and sharing knowledge with others. Perceived usefulness, perceived ease of use, subjective norm and facilitating condition have a positive effect on the attitude of farmers to used ICT. In order to increase ICT usage and encourage farmers to applied ICT, agencies or related departments should provide them with training in ICT related courses. The relevant departments should also facilitate access to information through mobile phones applications such as WhatsApp, Facebook or other social media. Other agencies should look at this upgrade the coverage access at this area so that farmers can use the phone and the internet to make a call or search for information from other farmers, supplier easier or websites in their field.